The socio-demographic profile associated with perinatal depression during the COVID-19 era - Katina Kovacheva; María F. Rodríguez-Muñoz; Diego Gómez-Baya; Sara Domínguez-Salas; Emma Motrico (BMC, 2023)
Abstract Background Coronavirus disease 2019 (COVID-19) has caused an increase in perinatal depression. The aim of this research was to identify which sociodemographic variables are related to the increase in perinatal depression due to the pandemic. In addition to estimating to what extent they predict perinatal depression, differentiating the prenatal and postnatal periods. Methods The sample consisted of 3,356 subjects, 1,402 in the prenatal period and 1,954 in the postnatal period. The Edinburgh Postnatal Depression Scale was used to assess depressive symptomatology. A subset of 14 questions was included to collect demographic data. Items from the Spanish version of the Coronavirus Perinatal Experiences Survey were also included. Results Experiencing the change of environment due to COVID-19 as negative and having a history of mental health predict perinatal depression, otherwise having higher education decreases the risk. In the prenatal stage having symptoms compatible with COVID-19 is a predictor of perinatal depression and having more than 3 years living together with the partner and being a housewife decreases the risk. In the postnatal stage being unemployed is a predictor of prenatal depression and being a first-time mother decreases the risk. Conclusions This study highlights the relevance of sociodemographic status. It is essential to be aware of the risk factors of perinatal depression, to make adequate prevention, and to create health policies to alleviate the consequences of the pandemic.